The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1152/ajpheart.1992.263.4.h1270
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic blood volume changes with lower body suction in humans

Abstract: We recorded blood and plasma mass density and hematocrit of antecubital venous blood in 12 subjects in the supine position before, during, and after 20-40 min of lower body subatmospheric pressure (LBNP) of -35 mmHg. Mass density values decreased during the first minutes of LBNP, indicating a transient 2.8% blood volume gain before they rose as expected. After LBNP, a pronounced further density increase, indicating a further 1.5% hemoconcentration, preceded the return toward control. This pattern suggests refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…As expected, the HR responses to LBNP in POTS patients were enhanced. This excessive tachycardia may be caused by central hypovolemia, because LBNP induces venous pooling and also accentuates extravasation within the interstitium of the leg, thereby reducing plasma volume (13), which may be exaggerated in POTS patients (34,36,37). Additionally, hypovolemia (8,26) and cardiac atrophy due to deconditioning (Refs.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, the HR responses to LBNP in POTS patients were enhanced. This excessive tachycardia may be caused by central hypovolemia, because LBNP induces venous pooling and also accentuates extravasation within the interstitium of the leg, thereby reducing plasma volume (13), which may be exaggerated in POTS patients (34,36,37). Additionally, hypovolemia (8,26) and cardiac atrophy due to deconditioning (Refs.…”
Section: Discussionmentioning
confidence: 99%
“…Hinghofer-Szalkay et al 22 found an average 2.8% increase in blood volume in 8 nonsyncopal subjects soon after application of -35 mmHg LBNP preceding the expected decrease in volume. This compensatory infusion of volume peaked in 2-5 min, then blood volume returned to control values after 4-8 min except for one subject in which this balance occurred at 13 min.…”
Section: Comparison Of Modeled and Experimentalmentioning
confidence: 94%
“…After the skin had been cleaned with alcohol swabs, pairs of electrodes (Q‐10‐25) were placed behind the right sternocleidomastoid muscle and corresponding to the upper left ribs in the mid‐axillary line, with each pair placed with an internal distance of 5 cm (23). This electrode placement was also used when correlation with changes in the central blood volume was evaluated (24–26). The outer two electrodes provided the electrical field, whilst the inner pair was sensing; such an evaluation of the central blood volume shows a correlation with the volume deficit during haemorrhage and following reperfusion in the pig that approaches 1.0 (27), and allows for the prediction of hypotension when the central blood volume is reduced, e.g.…”
Section: Methodsmentioning
confidence: 99%